Mechanical resistance and chemical characterization of Amazonian deteriorated woods in field tests - Batista, Lédio; Stangerlin, Diego Martins; Melo, Rafael Rodolfo de; Souza, Adilson Pacheco de; Silva, Eldalisley dos Santos; Pariz, Elisangela (Instituto de Ecología, A.C., 2021)
This study aimed to evaluate the mechanical strength and chemical composition of Trattinnickia rhoifolia (amescla), Parkia pendula (angelim), Erisma uncinatum (cedro), Apuleia leiocarpa (garapeira) and Mezilaurus itauba (itaúba) exposed to deterioration in field tests. To achieve this, wood samples were partially buried in outdoor and forest canopy, being exposed to deterioration for 360 days. The tests were carried out in the city of Sinop, state of Mato Grosso, Middle West of Brazil. Every 60 days, deteriorated wood was mechanically evaluated by the static bending tests, to obtain the modulus of elasticity and rupture, and hardness Rockwell. The chemical composition (extractives, ash, lignin, holocellulose and solubility in sodium hydroxide) were evaluated before and after the exposure to deterioration tests. Itaúba and garapeira wood presented lower change in mechanical resistance and chemical composition, in comparison to the other species, indicating a greater natural durability.